“Pelo progresso do paiz”: projetos para a educação de ingênuos na imprensa paulista em fins do século XIX - Lucas, Kadine Teixeira (2016)
The present work aims to investigate the projects for the education of the “ingenuous” (freeborn child of slaves) diffused on the printing-press of São Paulo between the promulgation of the “Free Womb Law” (1871) and the years that followed the abolition of slavery. Therefore, we analyse the way in wich the ideas about race and modernization were rellated to the pedagogical propositions for the child of slaves on the press vehicle that represented the ideology of white elite, called “Correio Paulistano” (1854-1942) and, in opposition to it, on two other journal of that period, “O Progresso – Orgam dos Homens de Côr” (1899) – wich we will call black press – and “A redempção, Folha Abolicionista” (1887-1899) -, wich we will identify as an abolitionist press